MENAVIGASI KELOMPOK RENTAN PERKOTAAN: PERAN FASILITATOR KAPAL PEREMPUAN DALAM MEMBERDAYAKAN PEREMPUAN MARGINAL DI JAKARTA - Septyana, Rossa Dwi; Indri Ajeng Setyoningrum (Journal of Practice Learning and Educational Development, 2026)
Marginalized women in urban areas face vulnerability due to social, economic, and gender inequalities that limit access to education, employment, social protection, and basic rights. This condition demands a contextual and sustainable empowerment approach, one of which is thru community-based non-formal education. This research aims to describe the role of facilitators from the KAPAL Perempuan Institute in empowering marginalized urban women thru the Sekolah Perempuan program in Jakarta. The research uses a descriptive qualitative approach with data collection techniques in the form of in-depth interviews, non-participatory observation, and documentation studies of facilitators, female school members, and institutional staff. Data analysis was conducted using the Miles and Huberman model. The research results show that facilitators play a strategic role in every stage of empowerment, namely the awareness stage thru the development of critical awareness of life experiences and gender inequality, the capacity-building stage thru gender-just education and strengthening local context-based leadership, and the empowerment stage thru cadre training, administrative mentoring, and women's rights advocacy. The role of the facilitator is not only technical but also transformative, serving as a bridge between women's experiences and critical knowledge. This research shows the role of facilitators in empowering urban marginalized women to the stage of empowerment; the facilitators successfully transformed their members into cadres for other vulnerable women.